QUALITY CHARACTERISTICS FERMENTED TILAPIA (Oreochromis niloticus) DIFFERENT CARBOHYDRATE SOURCE - Sari, N Ira; Dahlia, Dahlia; Octavian, Deby (Fakultas Perikanan dan Kelautan Universitas Riau, 2013)
The research was conducted in the Laboratory of Fish Processing Technology,Food Chemistry and Food Microbiology, Faculty of Fisheries and Marine ScienceUniversity of Riau. The objective of this study was to determine the characteristics offermented tilapia fermented with different carbohydrate sources. About 5 kg fishweighting 100 gr each was taken from a fish market in Pekanbaru. Two groups of fishwas fermented repeatedly using roasted rice and fermented bamboo shoot. The fish wasfermented at room temperature for 7 days. Quality characteristics of the fermented fishwas evaluated for sensory atributes (appearance, flavor, odor, and texture), chemicalvalue ( pH, moisture, NPN, lactic acid), and lactic acid bacteria count. The fish whichwas fermented with roasted rice was characterized by appearance (attractive, clean,yellowish color), flavor (sour and salty, typical fermentation), odor (acid/alcohol, lessfresh, typical fermentation) and texture (dense, compact, chewy). Chemical value: pH(5,91), moisture (53,6%), NPN (0,12 ml/gr), and lactic acid (1,23 ml/gr), lactic acidbacteria count (5,44 x 106). Fish fermented with fermented bamboo shoot wascharacterized by appearance (attractive, less clean, opaque), flavor (sour and salty, lesssavory, not typical fermentation), odor (acids and less alcohol, typical fermentation) andtexture (elastic, compact, chewy). Chemical value: pH (5,38), moisture (59,79%), NPN(0,19 %), and lactic acid (1,71 %), lactic acid bacteria count (8,167 x 106 colony/gr).Keywords: Fermented tilapia, roasted rice, and bamboo shoots